Study of the relation between testosterone levels and the severity of acne vulgaris among unmarried women at Al-Shati area, Libya: Study of the relation between testosterone levels and the severity of acne vulgaris among unmarried women at Al-Shati area, Libya - Sheeba, Abdullah Najim (International Journal of Pharmaceutical & Biological Archive, 2018)
Introduction: Acne vulgaris (AV) is long-lasting inflammatory illness of pilosebaceous unit and is clinically characterized by seborrhea and open and closed comedones, and in the severe cases, papules, pustules, nodules, deep pustules, and pseudocysts. The situation starts after adolescence and is a common skin disorder in adolescents and young grown person. Aim: The aim of this study was to evaluate the relation between testosterone levels and the states of AV among unmarried women. Materials and Methods: This study was conducted on 52 unmarried women, from which 26 women were with AV and 26 were used as control (age ranges were from 14 to 36 years). The patients were divided into three groups according to the severity of AV (sever, moderate, and mild). Results: Serum testosterone was significantly higher (P < 0.05) in severe and moderate acne patients, while the serum testosterone level shows no significant difference in females with mild acne disease when compared with that of female control group (P Ëƒ 0.05). Conclusion: The conclusion of the study found a significant association between serum testosterone and severity of AV, and there was no correlation between the severity of AV and patients ages.